Can Risk Stratification Based on Ultrasound Elastography of Background Liver Assist CEUS LI-RADS in the Diagnosis of HCC? - Li, Jiawu; Ling, Wenwu; Chen, Shuang; Yang, Lulu; Ma, Lin; Lu, Qiang; Luo, Yan (Frontiers in Oncology, 2021)
Objective: To explore whether risk stratification based on ultrasound elastography of liver background assists contrast-enhanced ultrasound liver imaging reporting and data system (CEUS LI-RADS) in diagnosing HCC. Materials and Methods: In total, 304 patients with focal liver lesions (FLLs) confirmed by pathology underwent CEUS and ultrasound elastography were included in this retrospective study. Patients with chronic hepatitis B (CHB, n=193) and non-CHB (n=111) were stratified by four liver stiffness measurement (LSM) thresholds. A LI-RADS category was assigned to FLLs using CEUS LI-RADS v2017. The diagnostic performance was assessed with the AUC, sensitivity, specificity, PPV, and NPV. Results: The mean background liver stiffness of HCC patients with CHB, HCC patients without CHB and non-HCC patients without CHB were 9.72 kPa, 8.23 kPa and 4.97 kPa, respectively. The AUC, sensitivity, specificity and PPV of CEUS LI-RADS for HCC in CHB patients with LSM ≥ 5.8 kPa, ≥ 6.8 kPa, ≥ 9.1 kPa, and ≥ 10.3 kPa were high, with corresponding values of 0.745 to 0.880, 94.2% to 95.3%, 81.3% to 85.7%, and 98.1% to 98.8%, respectively. Higher AUC and specificity for HCC was observed in non-CHB patients with LSM ≥ 9.1 kPa and ≥ 10.3 kPa compared to non-CHB patients with LSM ≥ 5.8 kPa and ≥ 6.8 kPa, with corresponding values of0.964/1.000 vs 0.590/0.580, and 100%/100% vs 60%/70%, respectively. Conclusion: CEUS LI-RADS has a good diagnostic performance in CHB patients regardless of the background liver stiffness. Furthermore, CEUS LI-RADS can be applied for non-CHB patients with a LSM ≥ 9.1 kPa.